Waste to Energy: Utilization of Eggshell Catalysts in the Production of Waste Cooking Oil-Based Biodiesel - Sister Sianturi; Gesha Desy Alisha; Febry Rahmadhani Hasibuan (Akta Kimia Indonesia, 2026)
This study aims to investigate the utilization of eggshell waste as a catalyst in biodiesel production from waste cooking oil within the waste to energy concept. The catalyst was synthesized through a calcination process to produce calcium oxide (CaO), which acts in the transesterification reaction. Biodiesel production was carried out by reacting waste cooking oil with methanol in the presence of CaO catalyst. The resulting biodiesel was analyzed for yield, chemical composition using GC–MS, and physical properties including viscosity and density. The results showed that the biodiesel yield reached 70%. GC–MS analysis revealed that the product was dominated by fatty acid methyl esters (FAME), such as methyl palmitate, methyl oleate, and methyl linoleate. The density value of 0.9429 g/mL met the SNI 7182:2015, while the viscosity value of 2.0821 cP was slightly below the minimum standard limit. Overall, this study demonstrates that eggshell waste has significant potential as an environmentally friendly alternative catalyst for biodiesel production from waste cooking oil, although further optimization is required to improve the quality of the produced biodiesel.